(4‐[6‐(4‐isopropoxyphenyl)pyrazolo [1, 5‐a]pyrimidin‐3‐yl] quinoline) is a novel inhibitor of autophagy. (5th September 2014) - Sheng, Yue; Sun, Bo; Guo, Wen‐Ting; Liu, Xiao; Wang, Yu‐Chun; Xie, Xin; Xiao, Xiao‐Lin; Li, Na; Dong, De‐Li
<x xml:space="preserve">Abstract</x> Background and Purpose Autophagy is an important intracellular degradation system, which is related to various diseases. In preliminary experiments we found that D4‐[6‐(4‐isopropoxyphenyl)pyrazolo [1, 5‐a]pyrimidin‐3‐yl] quinoline (DMH1) inhibited autophagy responses. However DMH1 also inhibits the signalling pathway activated by bone morphogenetic protein‐4 (BMP4). The aim of the present study was to elucidate the inhibitory effects of DMH1 on autophagy and the underlying mechanisms. Experimental Approach The effects of DMH1 on autophagy responses were evaluated in cultures of different cell types and with different stimuli to induce autophagy, using Western blots, transmission electron microscopy and fluorescent microscopy. Key Results DMH1 inhibited starvation‐induced autophagy in cardiomyocytes, HeLa and MCF‐7 cells, without involving the signalling pathway of BMP4. DMH1 inhibited aminoimidazole carboxamide ribonucleotide (AICAR)‐ and rapamycin‐induced autophagy in HeLa and MCF‐7 cells. DMH1 reversed starvation‐ and AICAR‐induced inhibition of Akt, mammalian target of rapamycin (mTOR) and p70S6 kinase (S6K), and reversed rapamycin‐induced inhibition of mTOR and S6K. DMH1 reversed starvation‐induced decrease of the phosphorylated form of glycogen synthase kinase‐3 in MCF‐7 and HT29 cells. Activation of Akt and inhibition of autophagy induced by DMH1 were antagonized by an Akt specific inhibitor or by small interfering RNA for Akt in HeLa cells. Conclusion and Implications DMH1 inhibited cellular autophagy responses in a range of cell types and the underlying mechanisms include activation of the Akt pathway.